ANALISIS KOMPETENSI PERSONAL MAHASISWA TINGKAT AKHIR SEBAGAI SARANA OPTIMALISASI BIMBINGAN TUGAS AKHIR - Andi Wibowo Wibowo (Program Studi PGSD STKIP PGRI Banjarmasin, 2019)
This study aims to map the personal competencies of final-year students in the Faculty of Psychology and Education Raden Rahmat Islamic University. This mapping was carried out as an evaluation for the final project guidance activity. This study uses a quantitative approach. Research procedures include preliminary studies, research planning, data collection, data analysis and interpretation, and drawing conclusions. The subjects were 97 of 7th semester student in Faculty of Psychology and Education. Data collection techniques using written tests. Data analysis techniques using simple quantitative analysis. The results showed that the personal competence of Faculty of Psychology and Education students was 17% (16 students) in the very good category, 76% (76 students) in the good category, and 7% (7 students) in the moderate category. For students with sufficient personal competence, it is advisable to use a developmental approach in the final project guidance activities.